Analysis of Ferroptosis-Mediated Modification Patterns and Tumor Immune Microenvironment Characterization in Uveal Melanoma - Jin, Yi; Wang, Zhanwang; He, Dong; Zhu, Yuxing; Gong, Lian; Xiao, Mengqing; Chen, Xingyu; Cao, Ke (Frontiers in Cell and Developmental Biology, 2021)
Uveal melanoma (UVM) is one of intraocular malignancies in adults with approximately 50% of patients developed metastatic disease and suffered from a poor prognosis. Newer field of immunotherapies have rapidly emerging and have yielded impressive results. Emerging evidence implicated that ferroptosis is a novel type of cell death which may mediate the tumor-infiltrating immune cells to influent on anticancer immunity. In this study, we firstly selected 11 ferroptosis regulators in UVM samples from the training set (TCGA and GSE84976 databases) by the Cox analysis. Then we divided these molecules into module A and B based on the STRING database and used the Consensus Clustering analysis to classified genes into two clusters in both two modules. According to the GO, KEGG, and GSEA analysis, the results revealed that the clusters in module A was remarkably related to immune-related pathways. Next, we applied the ESTIMATE and CIBERSORT algorithm and found these ferroptosis-related patterns may affect the proportion of TME infiltrating cells so that to mediate the tumor immune environment. Additionally, for further developing the prognostic signatures based on the immune landscape, we established a six-gene-regulator prognostic model in training set and successfully re-verified in the validation set (GSE44295 and GSE27831). Subsequently, we further identified the key molecules, including ABCC1, CHAC1, and GSS, which was associated with poor OS, PFS, DSS, and PFI. Moreover, we constructed a competing endogenous RNA (ceRNA) network for further elucidate the mechanisms, which consist of 29 lncRNAs, 12 miRNA and 25 ferroptosis-related mRNAs. In conclusion, our finding indicated the ferroptosis-related genes may view as potential biomarkers to provide novel insight into UVM prognosis and deciphered the underlying mechanisms in tumor microenvironment characterizations.